The Culture of Food Security in the Romanian Penitentiary System (Annals of the University of Bucharest. Geography Series, 2025)
A special place in the national security strategies is also occupied by the food security/safety, analyzed as a component of the economic security. The National Administration of Penitentiaries (ANP), a public state organization, was receptive to this problem. The receptivity in the Romanian penitentiary system comes from the fact that the institution is a follower of a strict functioning regulation, considering that its observance represents a simple and efficient way of achieving control and self-control. Thus, it respects first of all, the strategies of the HACCP system (Hazard Analysis Critical Control Point), the legal framework imposed by the international standard ISO 22000 and the Strategy of food safety and security in Romania (currently being respected the conditions proposed by the approved version for the period 2016–2035). The present study is intended to be a qualitative and suggestive synthesis of the issues related to food security/safety versus food insecurity, food quality and hygiene, and the waste management, as a result of this action in a closed environment, such as that developed by a penitentiary.
Keywords: food; ISO; legislation; person deprived of liberty; penitentiary system; regulations